Examination of the impact of possible distribution network design on network losses - Cao,DM; Pudjianto,D; Strbac,G; Ferris,R; Foster,I; Aten,M (2009)
In the present climate where reducing CO2 emissions is of increasing importance, reducing losses is becoming one of the important factors considered in distribution network design and operational strategies. This paper simulates various potential network design scenarios using generic distribution network models and evaluates their impact on network losses.